ISLAMISASI ILMU EKONOMI JENJANG MADRASAH ALIYAH (ANALISIS ISLAMIC WORLDVIEW MATERI AJAR ILMU EKONOMI) - Nufus, Dewi Hayati; Tanjung, Hendri; Tamam, Abas Mansur (Jurnal Dakwah Tabligh, 2022)
The aim of this research is to construct Islamic worldview concepts as an effort to Islamization of economics at Madrasah Aliyah by content analysis which refers to sources of Islamic knowledge, in order to inculcate Islamic values and teachings in students at Madrasah Aliyah. The research uses a qualitative method with a library research approach. The Design of this study is to employ the content analysis on the common use economics textbook for Madrasah Aliyah and supported by previous research related to the theme. Discussion section on the concepts of Islamization of Economics. The framework of The Islamic worldview in economics as teaching material is formed by the Tawhid concepts, the Islamization of economics, and the relevance of The Islamic worldview with the Islamization of knowledge, particularly economics. The last section focuses on the implementation Of The Islamic worldview in subject material economics at Madrasah Aliyah. The research has found many contradistinguish issues in Islamic perspectives of economics material teaching in the economics textbook for the tenth grades, which is commonly used by the tenth grades student at Madrasah Aliyah. The contradistinguish issues are about the definitions and goals of economics, its principles, its foundations of economics, and the sources of economics including the pillars of economics. The values of this study provide an Islamic worldview as a supplement teaching material which accomplishes the body of material teaching of economics should be in Madrasah Aliyah. The proceed of this work has qualified prospects to be promoted as an Islamic Economics teaching material for tenth grades Social Science Madrasah Aliyah students.